Tillvaratagande av GROT i skärgårdsnära miljö - Söderström, Björn (SLU/Dept. of Forest Products, 2006)
The main aim of this study was to investigate and compare different methods for the extraction of forest fuel from environments close to an archipelago. The study was based on relevant literature and published reports as well as personal communications. Forestry has traditionally been characterized by intense efforts to rationalize and mechanize the cutting technique used for timber and pulpwood. In line with the increasing importance of forestry, more concentrated efforts can be expected in the area of techniques and methods, especially for the above-mentioned product lines. In Sweden, forestry is of major importance and the Swedish economy and standard of living have mainly been created based on the revenues generated from it. Thus, it is vital that Swedish forests are harvested in an efficient and responsible manner. The demand for biofuel is growing and today accounts for 15% of total Swedish energy production, a share that will probably increase. This study is based on three research questions, which are described under the heading of Aim. The results reveal that the most profitable method for handling forest fuel is the traditional one, which is also the most commonly used method in southern Sweden, namely the stockpiling of logs in a clearing by means of forwarders followed by splintering at the place from where they will be distributed. Today, the high cost of barge transport required for the extraction of forest fuel in an archipelago environment renders such operations unprofitable. In this study, the EU subsidies available for the extraction of forest fuel in an archipelago environment have not been taken into account. However, even if such subsidies were to be included, it would still be difficult to achieve profitability.